The Lack of RR Lyrae Variables in Ultrafaint Dwarf Galaxy Sextans II - Chow-Choong Ngeow; Anupam Bhardwaj (The Astronomical Journal)
RR Lyrae in ultrafaint dwarf (UFD) galaxies, if found, would be valuable to constrain the distances of these UFD. In this work, we report our search of RR Lyrae in a recently discovered UFD—Sextans II. Based on multiband (griz) time-series archival DECam imaging data, we do not find any RR Lyrae in Sextans II. On the contrary, the sparse multiband DECam light curves allowed recovery of a known foreground RR Lyrae, BB Sex, which happened to fall within the DECam images, and its pulsation period was correctly identified. Therefore, it is possible that Sextans II lacks RR Lyrae, similar to several other fainter UFDs (with M _V  ≳ −5.0 mag) that do not have RR Lyrae.